2016
DOI: 10.18553/jmcp.2016.22.12.1394
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Disease-Modifying Therapies for Multiple Sclerosis

Abstract: TEVA provided funding for this study and had the option to review the manuscript. The authors retained autonomy in the determination of the final content of this work. Study concept and design were contributed by Carlin, Anderson, and Higuera. Data interpretation was primarily performed by Higuera and Carlin, along with Anderson. The manuscript was written and revised by Higuera, Carlin, and Anderson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 34 publications
11
82
2
Order By: Relevance
“…Compared to men, women in this study were 24% less likely to be adherent, a trend also observed recently by Higuera et al, who found that women with MS had a 5.5 percentage-point lower probability of being adherent (as measured by the MPR) than men 35. Although the reasons for poorer adherence among women remain speculative, one explanation is that more intense medication use may compromise adherence 36.…”
Section: Discussionsupporting
confidence: 79%
“…Compared to men, women in this study were 24% less likely to be adherent, a trend also observed recently by Higuera et al, who found that women with MS had a 5.5 percentage-point lower probability of being adherent (as measured by the MPR) than men 35. Although the reasons for poorer adherence among women remain speculative, one explanation is that more intense medication use may compromise adherence 36.…”
Section: Discussionsupporting
confidence: 79%
“…We found significant differences in TB in patients receiving oral versus injectable therapies. This has been previously described [30,31] and is an additional factor that must be taken into account when choosing specific disease-modifying treatments for the individual patient. We also detected significant correlation between TBQ scores and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, no adherence is defined as the "failing to fill prescriptions, delaying prescription fills, reducing the strength of the dose taken, and or reducing the frequency of administration. It can also include the failure to keep appointments or to follow the recommended lifestyle or dietary changes [5,6]." The availability of DMTs in low-to middle-income countries and adherence of MS patients to a medication that is not curing their disease are two critical challenges nowadays.…”
Section: Introductionmentioning
confidence: 99%